Vexillology on the electrocardiogram. South Africa ́s flag sign - Estupiñan-Paredes, Ruth N. (2022)
The electrocardiogram (ECG) is a test that will allow making life-saving decisions. It has different patterns, and differential diagnoses, like the pattern of acute coronary syndrome with an elevation of the high lateral ST segment, which is called the sign of the flag of South Africa. We present the case of a 44-year-old patient presented with typical chest pain; the ECG showed ST-segment elevation in the DI, DII, AVL – V2, and ST depression in DIII, corresponding to an acute coronary occlusion with a compromise of the lateral segment of the heart. This ECG pattern is known as the flag sign of South Africa. The early recognition allowed the decision to perform immediately pharmacological reperfusion therapy and rescue angioplasty.